Augmenting the seismic performance of masonry models using polypropylene band and steel wire mesh through shaking table testing. (August 2020) - Banerjee, Susanta; Nayak, Sanket; Das, Sreekanta
Abstract: The seismic vulnerability of unreinforced masonry (URM) structures was observed during the past seismic events, which caused a huge loss of life and property. However, URM buildings are quite common in developing countries like India as they offer cheap shelters to people with low income. An easily implementable strengthening technique with cost-effective materials for enhancement of the seismic behaviour of URM building is of utmost importance. Hence, this study was carried out to develop a technique to improve the strength and ductility of URM buildings. Clay bricks and eco-friendly fly-ash bricks were used for the construction of the building models. Brick sizes were reduced to half so that the scale-down building model can be constructed for testing. The building models were tested in a uni-directional shaking table using swept sine motions. The experimental investigation was categorized in three phases. In the first phase, the effect of diaphragm action on seismic behaviour of masonry building was investigated by providing the flat reinforced concrete slab and pitched timber truss as a roof on top of the building. The second phase focused on the enhancement of the seismic behaviour of the URM wall by strengthening with two cost-effective materials, such as polypropylene (PP) band and steel wire mesh (WM). In the third phase, cracked (damaged) URM walls were repaired and retrofitted with wire mesh. It was observed that both the strengthening materials were effective in improving the ductility of the URM buildings.